Adolescent human papillomavirus vaccination in the United States: Opportunities for integrating pharmacies into the immunization neighborhood - Joseph P. Fava; Jacob Colleran; Francesca Bignasci; Raymond Cha; Paul E. Kilgore (Human Vaccines & Immunotherapeutics, 2017)
Human Papillomavirus (HPV) vaccination faces several barriers, including a social stigma which carries religious and philosophical implications among parents of adolescents as well as young adults. Hundreds of immunization interventions and programs have been developed to address these factors and boost HPV vaccination rates in the United States. We sought to review the existing literature highlighting barriers to HPV immunization, as well as programs targeting increased HPV vaccine uptake in effort to develop novel vaccination initiatives. The most impactful barriers identified were parental stigma and low quality of provider recommendations for the vaccine. Despite the implementation of many HPV initiatives, outcomes of these programs are largely limited to modest improvements in vaccine uptake in small, homogeneous populations. We describe pharmacies as distinctly advantageous but underutilized resources within the immunization neighborhood and propose a novel concept to improve vaccination rates as well as reduce HPV-related disease burden in all demographics.